Targeting c-MET by Tivantinib through synergistic activation of JNK/c-jun pathway in cholangiocarcinoma - Wei, Kai; Li, Mao; Zöller, Margot; Mehrabi, Arianeb; Hoffmann, Katrin (Cell death & disease, 2019)
Clinical treatment options for human cholangiocarcinoma (CC) are limited. c-MET, a high-affinity receptor for hepatocyte growth factor (HGF), is deregulated in many cancers. Its role in cholangiocarcinogenesis remains unclear. In current study, 23 corresponding tumor- and non-tumor tissues, taken from patients with intrahepatic (iCC) and perihilar cholangiocarcinoma (pCC), who underwent liver resection, were analyzed. The relationship of clinicopathological features and c-MET, as well as c-jun N-terminal kinase (JNK) was evaluated. The anti-tumor effects of Tivantinib, a small-molecule inhibitor with potent activity against the c-MET kinase, was investigated in three human CC cell lines, namely HUCC-T1, TFK-1, and EGI-1. In comparison with the results obtained in non-tumor tissue samples, c-MET was overexpressed in 91.3 % of tumor tissues (p < 0.01). The JNK expression was higher in tumor tissue compared with the corresponding non-tumor tissue sample in 17.4% patients (p < 0.01). The inhibition of aberrant c-MET expression in human CC cell lines was achieved by blocking the phosphorylation of c-MET with Tivantinib. Notable losses in cell viability and colony-forming capability were detected (p < 0.01). Synergistic activation of the JNK/c-jun pathway was demonstrated after Tivantinib treatment. Knockdown of the JNK by siRNA or competitive binding of c-MET receptor by stimulation with HGF-antagonized anti-tumor effects of Tivantinib was observed. Our data suggest that inhibition of c-MET could be a possible alternative approach for the treatment of human CC, for which Tivantinib may an effective inhibitor. The synergistic activation of the JNK/c-jun pathway contributed to the elevated apoptosis in CC cells via treatment with Tivantinib.